Physiological study of foliar feeding with the amino acid glycine and thiamine for date palm seedlings (Phoenix dactylifera L.) - Ati, Muntaha A.; Awad, Khairullah; Obaid, Nada A. (Basrah Journal Of Date Palm Research, 2024)
Good nutrition depends mainly on the balance between the nutrients that the plant needs, whether these elements are already available in the soil or added in the form of foliar fertilizers for the plant. It is preferable to the plant, provided that other necessary factors are available. Therefore, this experiment was conducted in order to study the effect of spraying with the amino acid Glycine and thiamine on date palm seedlings from the seeds to determine their effect on some morphological and chemical properties. The concentrations of 50 and 100 mg.L-1 were sprayed. With the distilled water and the diffusion material only, the seedlings were sprayed twice the first time in March. The period between the two weeks was two weeks. Results showed that the paper spray with vitamin B concentration of 50 mg.L-1 increased the content of the leaves of the amino acid proline, For vitamin B-100 mg.L-1 leaves in the content of leaves of free amino acids, total dissolved phenols and dissolved protein.